The Meaning of Breast Cancer Patients’ Experience in Hospital X: a Viewpoint From Patient Centered Care - Farida Rozany; Indah Winarni; Viera Wardhani (Universitas Muhammadiyah Yogyakarta, 2019)
Patient experience is a significant factor in improving hospital service quality. This study aims to determine the meaning of treatment received by breast cancer patients during the treatment period. In the treatment of breast cancer, the patients require a personalized service or patient-centered care. This research is a qualitative analysis with phenomenology approach. Informants in this study were breast cancer patients who underwent chemotherapy treatment and had a mastectomy. Data were obtained through in-depth interviews in patients with breast cancer. The results of the study revealed there are 10 themes, namely worrying about something uncomfortable in the body, resigning to the doctor's recommendations, feeling comfortable and uncomfortable in the service received, feeling stress after recognizing the disease suffered, feeling fearful to the disease, experiencing pain before and after treatment, obtaining encouragement, refraining from thinking that slows down the healing, feeling of having no choice over the disease, and feeling of not obtaining explanation. There is relevance between theme and patient-centered care.